The mechanism of paclitaxel induced damage on placental trophoblast cells - Yang Yu; Jia-lei Zhu; Jun-min Li; Jing Tang (BMC, 2024)
Abstract Objective Chemotherapy during pregnancy has a certain risk of causing a series of complications, such as miscarriage, premature birth, or fetal growth restriction, although the relationship between these complications and chemotherapy is currently unclear. This experiment focuses on the possible damage mechanism of the chemotherapeutic drug paclitaxel on placental trophoblast cells, and explores whether chemotherapy can affect pregnancy outcomes by directly damaging placental tissue. Methods This study explored the mechanism of paclitaxel induced damage on placental trophoblast cell lines JEG-3 and BEWO through immunofluorescence staining, Western blot experiments, cell flow cytometry, Seahorese cell metabolism experiments, and mouse modeling verification. Results The experiment found that paclitaxel could induce JEG-3 and BEWO cells to produce reactive oxygen species (ROS), and elevate the ratio of Bax/Bcl-2 expression. Besides, paclitaxel mediated the reduction of mitochondrial membrane potential in JEG-3 and BEWO cells, causing damage and leading to mitochondrial autophagy and the occurrence of unfolded protein response. Paclitaxel inhibited the glycolysis rate of JEG-3 and BEWO cells, and leaded to impaired mitochondrial function, including decreased basal respiratory values, decreased respiratory reserve capacity, and proton leakage. In pregnant mice with tumor modeling, paclitaxel could cause DNA damage in placental tissue cells, and might lead to apoptosis of chemotherapy mice placental tissue cells and impairment of normal physiological functions. Conclusion Paclitaxel may directly or indirectly affect the normal physiological functions of placental trophoblast cells, including energy metabolism and protein synthesis dysfunction, which may be related to the adverse pregnancy outcomes caused by paclitaxel chemotherapy.